The Effects of Honor Culture on Emotional Suppression and Psychological Well-being in Pakistani Youth - Sana Munawar; Asif Bilal; Sidra Mustaqeem; Awais Ur Rahman (Dialogue Social Science Review (DSSR), 2025)
In countries like Pakistan, where collectivism exists, honor culture is significant in regulating emotions and one's psychological wellbeing. The need to fulfill cultural obligations pertaining to honor often results in emotional suppression which can be detrimental to mental health, particularly for the youth. This research aims to explore the impact of honor culture on emotional suppression and psychological wellbeing of the Pakistani youth with respect to gender differences and coping strategies. A qualitative research design using the focus group approach was adopted. Twenty-four participants aged 18-25 were sampled purposively from six major cities of Pakistan, Islamabad, Lahore, Karachi, Peshawar, Quetta, and Multan, using a form of non-probability sampling. Key themes were formulated from the data set using thematic analysis through NVivo software and were related to cultural norms, emotional suppression, and psychological suffering. Findings showed that, in the case of males, strict adherence to honor culture led to ‘greater emotional suppression’ because of rigid gender norms. Social and familial norms of reputation greatly inhibited emotional expression which increased stress and psychological suffering. On the other hand, some participants reported religion and peer support as adaptive coping strategies for emotional difficulties. Emotional suppression also differed among urban and rural participants. The culture of honor significantly impacts emotional regulation and the psychological well-being of Pakistani youth, often exacerbating distress due to the need for conformity. To promote healthier emotional expression and resilience, mental health interventions that are sensitive to the culture are needed.